Creation of Novel Protein Variants with CRISPR/Cas9-Mediated Mutagenesis: Turning a Screening By-Product into a Discovery Tool. - Katherine F Donovan; Mudra Hegde; Meagan Sullender; Emma W Vaimberg; Cory M Johannessen; David E Root; John G Doench (PLoS ONE, 2017)
CRISPR/Cas9 screening has proven to be a versatile tool for genomics research. Based on unexpected results from a genome-wide screen, we developed a CRISPR/Cas9-mediated approach to mutagenesis, exploiting the allelic diversity generated by error-prone non-homologous end-joining (NHEJ) to identify novel gain-of-function and drug resistant alleles of the MAPK signaling pathway genes MEK1 and BRAF. We define the parameters of a scalable technique to easily generate cell populations containing thousands of endogenous allelic variants to map gene functions. Further, these results highlight an unexpected but important phenomenon, that Cas9-induced gain-of-function alleles are an inherent by-product of normal Cas9 loss-of-function screens and should be investigated during analysis of data from large-scale positive selection screens.